A Feasibility study on SPACE Call-in Home Spa - Buenviaje, Arlene C. (College of Engineering, 2003)
The following study was conducted to establish the overall feasibility of SPACE Call-in Home Spa. The company provides spa services on the customers' homes, bringing in all the necessary equipment and personnel. The services to be offered are the following: massages (Thai, Shiatsu and Swedish), facials, hand spa, foot spa, and waxing. Packages with combinations of these services will also be made available. A market study was made to test the receptiveness of society to the concept of a call-in spa and to test its marketability to the public. Here, it was concluded that Pasig would be the most suitable location since it has the greatest population density of classes A & B. SPACE Call-in Home Spa was also found to potentially dominate the market share of Spa services at 50.28%. The overall estimated marketing budget for the next five years was estimated at PHP 5,812,122.80. The technical analysis of this study provided details on the necessary equipment, personnel, and other factors that would be needed in setting up and operating the company. It was determined that the company will be set up as a closed-type of corporation. SPACE will be hiring a total of 52 employees. It will also be purchasing several equipment needed for providing spa services, which includes five second-hand vans. The financial analysis considered the overall profitability of putting up the company, making use of financial measures. The total project cost was estimated at PhP 2.4 million. It was recommended that the project be financed using purely equity financing. The financial measures showed positive signs for the company's profitability. A positive net worth was obtained, and an internal rate of return (IRR) of 18.39% was obtained. The social profitability analysis weighed the benefits to society of the establishing the company versus its costs. The benefits were estimated to have a positive net worth as well as an IRR of 80.35%, proving that the project was socially feasible. Conducting the entire feasibility study proved that SPACE Call-in Home Spa is indeed feasible. It was also made apparent that the company would be a worthwhile investment for individuals/establishments willing and able to finance the project.